Netflix and Dilemma of Content Regulation in Malaysia - Muhammad Adnan Pitchan, Asma Md. Isa, Wan Amizah Wan Mahmud, Wan Idros Wan Sulaiman (International Journal of Advanced Science and Technology, 2019)
This study represents the dilemma encountered by Malaysian audiences on the issue of Netflix content through Internet streaming. Malaysia has various laws that regulate the functioning of media in the areas of printing, broadcasting and telecommunications. However, the government’s assurance through the Communications and Multimedia Act 1998 will not impose any filter on the Internet has opened the democratic space to the new media world. This freedom has triggered a public outcry over content streamed through the Netflix platform. Netflix, as one of the leading global media over-the-top (OTT) provider, provides its published material as well as aggregated content from publishers from various countries that are not in line with the practice of content regulation in Malaysia. The findings of this study revealed the experiences and views of adults on Netflix’s subscription motives, the relationship between the Internet and Netflix’s programmes as well as discovered audiences understanding on the regulatory and censorship concepts in Malaysia. In conclusion, this would lead to some suggestions for further consideration. Keywords: dilemma, convergence technology, content regulation